2004
DOI: 10.1194/jlr.m400345-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms mediating insulin resistance in transgenic mice overexpressing mouse apolipoprotein A-II

Abstract: We previously demonstrated that transgenic mice overexpressing mouse apolipoprotein A-II (apoA-II) exhibit several traits associated with the insulin resistance (IR) syndrome, including increased atherosclerosis, hypertriglyceridemia, obesity, and IR. The skeletal muscle appeared to be the insulin-resistant tissue in the apoA-II transgenic mice. We now demonstrate a decrease in FA oxidation in skeletal muscle of apoA-II transgenic mice, consistent with reports that decreased skeletal muscle FA oxidation is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
18
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
8
18
1
Order By: Relevance
“…Treatment of the apoAIItg mice with an insulinsensitizing PPAR␥ agonist ameliorated the insulin resistance and hypertriglyceridemia (20). This suggested that the hypertriglyceridemia was mostly a consequence of the insulin resistance, consistent with the hypothesis described above.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Treatment of the apoAIItg mice with an insulinsensitizing PPAR␥ agonist ameliorated the insulin resistance and hypertriglyceridemia (20). This suggested that the hypertriglyceridemia was mostly a consequence of the insulin resistance, consistent with the hypothesis described above.…”
supporting
confidence: 82%
“…Additional evidence for other physiologic effects of apoAII has come from genetic studies in both humans and mice, which suggest a role for apoAII in triglyceride and free fatty acid metabolism (8 -10). Subsequently, studies of genetically modified mice carrying a transgene for either human or mouse apoAII (3,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), as well as apoAII knockout mice (22), confirmed a complex metabolic role for apoAII, including a rather profound effect on plasma triglyceride concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Total cholesterol, HDL, triglycerides, and free fatty acid concentrations were determined as described previously (26). HDL-cholesterol was quantitated after precipitation of VLDL and LDL with heparin and manganese chloride.…”
Section: Plasma Lipid and Glucose Assaysmentioning
confidence: 99%
“…The resulting cDNA was amplified with SYBR Green PCR Master Mix (Applied Biosystems, Foster City, CA, USA) and the appropriate forward and reverse primers (Table 1; 20 pM) in an ABI 7300 Real-Time PCR System (Applied Biosystems). Thermal cycling parameters included a denature step of 95°C for 10 min and (Castellani et al 2004). Fold change was calculated using the DDCt method.…”
Section: Protein Isolationmentioning
confidence: 99%